Revealing Nadiem Makarim’s Communication Strategy in the Cancellation of the 2024 UKT Increase: A Review of Functional Systemic Linguistics - Mariana, Ana; Otoluwa, Moon Hidayati (Language Development Center, 2024)
Background: Systemic Functional (LSF) in speech discourse analysis LSF is a linguistic approach that focuses on the use of language in social contexts and the contexts in which it is used. linguistic approach that focuses on the use of language in social contexts and their social context and its functions that enable the disclosure of important meanings to the speech comprehensively, including ideational, interpersonal, and textual meanings. including ideational, interpersonal, and textual meanings. Purpose: This study analyzed Nadiem Makarim’s speech on the cancellation of the Single Tuition Fee (UKT) increase in 2024 using the Systemic Functional Linguistics (SFL) approach. Method: This research used a descriptive qualitative method. The data source was the video text of Nadiem Makarim’s speech in 2024. The data collection procedure was listening and note-taking. The data analysis techniques were reduction, presentation, interpretation using the SFL approach, and drawing conclusions. Results and Discussion: The results showed that Nadiem’s speech was dominated by material and mental processes that reflected the concrete actions of the government and its beliefs in overcoming the issue of rising tuition fees. The sentence modes used were mostly declarative, aiming to provide information and attract the audience’s sympathy. The dominant modalities were those of belief and certainty, which illustrated Nadiem’s optimism towards the policies taken. Conclusions and Implications: The conclusion of this study shows that the LSF approach can be applied in learning text analysis to help students understand the context, structure, and meaning of texts more deeply. in more depth. This research makes a practical contribution to the method of teaching methods of text analysis in educational settings, opens up opportunities for further research, and enriches the literature on policy speech analysis. and enriches the literature on policy speech analysis in education.